A composite biomarker based on early dynamic changes in lactate dehydrogenase and PD-L1 expression enhances outcome prediction for immunochemotherapy in HER2-negative advanced gastric cancer - Zhang, Yue; Tian, Yang; Wei, Xiaoli; Bai, Lu; Song, Meiqi; Guo, Yuanzhi; Liu, Tianlai; Li, Xing; Shan, Weiqi; Wu, Huaxing; Han, Yu (Frontiers in Immunology, 2026)
IntroductionCurrent biomarkers for immunochemotherapy in HER2-negative advanced gastric cancer (AGC) exhibit inadequate predictive accuracy. Therefore, the development of innovative methodologies is imperative for improving patient selection.MethodsIn this retrospective biomarker study, a cohort of 107 patients with HER2-negative AGC undergoing first-line immunochemotherapy was examined. Serum biomarkers were serially assessed at baseline and after two treatment cycles. Univariate and multivariate Cox regression analyses, as well as ROC curve analysis, were employed to identify prognostic serum dynamics. A composite biomarker integrating dynamic changes in lactate dehydrogenase (LDH) and a combined positive score (CPS) was developed and validated. Additionally, exploratory genomic profiling was performed.ResultsIn this study, dynamic changes in LDH were identified as an independent prognostic factor. An increase in LDH of ≥26% after two treatment cycles was associated with significantly poorer progression-free survival (PFS: 5.33 vs. 8.93 months; HR: 2.585, P< 0.001) and overall survival (OS: 13.13 vs. 19.63 months; HR: 2.689, P< 0.001). Consistent results were observed in landmark analyses at the two-cycle timepoint, with significant differences in PFS-landmark (PFS-landmark: 5.17 vs. 8.40 months; HR: 2.450, P< 0.001) and OS-landmark (OS-landmark: 11.76 vs. 19.20 months; HR: 2.538, P< 0.001). Combining LDH dynamics with baseline CPS overcame the predictive limitations observed in patients with CPS<5. The subgroup within the composite biomarker (baseline CPS<5 plus LDH elevation ≥26% after two cycles) demonstrated poor prognosis and high risk of early disease progression in survival analysis (median PFS: 4.43 months; median OS: 12.26 months). The robustness of this biomarker was supported by ROC and calibration curves. Additionally, exploratory genomic analysis suggested potential prognostic implications of specific KRAS mutant subtypes and co-mutation patterns. However, validation of these findings is warranted through prospective, multi-center-controlled cohort studies due to constraints related to sample size.ConclusionIn HER2-negative advanced gastric cancer, a ≥26% increase in LDH following two treatment cycles serves as an independent prognostic risk factor. Combining baseline CPS with early LDH dynamics improves the identification of patients with aggressive disease and poor initial treatment response, thereby facilitating closer monitoring and prompt therapeutic reassessment for more personalized management.